2011
DOI: 10.4314/aipm.v5i2.64032
|View full text |Cite
|
Sign up to set email alerts
|

Self medication amongst general outpatients in a Nigerian community hospital

Abstract: Aim:This study was designed to determine the proportion of general out patients who practice self medication, the drugs employed and the reasons for resorting to self medication.Methodology:This study was conducted between June and December, 2007 at the General Outpatient Clinic of the Federal Medical Centre, Owo, Ondo State, Nigeria. Two hundred consenting respondents were selected by simple random sampling and interviewed with the aid of semi structured questionnaire by the authors with three assistants. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
66
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 8 publications
14
66
1
Order By: Relevance
“…Such assumptions for self-medication have been cited. 4,6 This is a dangerous assumption as minor ailments that could be managed by a health professional could easily be mismanaged through self-medication. Financial constraint, experience from previous ocular episode, quick relief, longer waiting time at health facilities, lack of trust in medical services, advice from neighbours, and distance to health facilities are other reasons for which ocular self-medication was practiced.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Such assumptions for self-medication have been cited. 4,6 This is a dangerous assumption as minor ailments that could be managed by a health professional could easily be mismanaged through self-medication. Financial constraint, experience from previous ocular episode, quick relief, longer waiting time at health facilities, lack of trust in medical services, advice from neighbours, and distance to health facilities are other reasons for which ocular self-medication was practiced.…”
Section: Articlementioning
confidence: 99%
“…[3][4][5] The practice of self-treatment is a vital part of local medical traditions of African people, where laypeople are used to taking treatment into their own hands on regular basis. 6 In various situations, familiar illnesses are dealt with by common people (with no medical background) on their own. It is only when the illness shift towards chronicity that people seek expert advice, be it from a local healer or a biomedical experts.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] The most important reason for increase in trend of selfmedication is easy availability of all categories of medicines, OTC, prescriptions only or even schedule X drugs without prescription. It is understandable that a significant proportion of the respondents in our study used analgesics either alone or in combination with other drugs without prescription as common analgesics can be bought without prescription in the community.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Afolabi in a study of market women in a suburban community of Lagos, Nigeria reported 95-98% 24 ; Omolase et al established that 79% of ophthalmic patients 25 and 85% of patients in the general out patients clinic 26 22 respectively engaged in self medication without prescription or medical advice. However, other studies revealed a much lower prevalence for self-medication.…”
Section: Scope and Distributionmentioning
confidence: 99%
“…People who self medicated reported taking one or several medications and more often one or two medications were involved 20,26,33,116 . Individuals sometimes self administer medications via drug identification.…”
Section: Self Medication -How and Whenmentioning
confidence: 99%